Shaping beta diversity in arid landscape through native plant species contributions: synergy of climate, soil, and species traits - El-Barougy, Reham Fekry; Bersier, Louis-Félix; Gray, Sarah M.; El-Keblawy, Ali; Galal, Tarek; Ullah, Fazal; Elgamal, Ibrahim A.; Dakhil, Mohammed A. (Frontiers in Plant Science, 2025)
Understanding how species traits, climate aridity, and soil resources interact to influence beta diversity is critical for predicting changes in plant community composition. This study aims to investigate how these interactions shape species contributions to spatial turnover and beta diversity, focusing on the unique dryland ecosystems of the Saint Katherine Protectorate (SKP) in Egypt. To address this, we analyzed data from 84 vegetation plots, considering the direct and indirect effects of climatic aridity, soil resources, and species traits (e.g., plant height, leaf production, specific leaf area), as well as the relative abundance of C3 plants and phylogenetic diversity on species contribution to beta diversity (SCBDeff). Using Generalized Linear Models (GLMs) and Structural Equation Modelling (SEMs), the results revealed complex indirect effects of aridity and soil resources on SCBDeff mediated by plant traits. SCBDeff was positively influenced by climatic aridity, particularly in species with greater phylogenetic distance, taller plants, high leaf production, and a higher relative abundance of C3 plants. Conversely, specific leaf area (SLA) had a negative effect. Phylogenetic diversity emerged as a significant driver of beta diversity, with distantly related species contributing more due to functional differentiation and niche partitioning. The findings emphasize the critical role of species traits and environmental conditions in shaping beta diversity. These insights can inform conservation strategies aimed at enhancing ecosystem stability under shifting climatic conditions, particularly in dryland environments where species adaptive traits play a pivotal role.